The Cooperative development authority program in the national capital region, its implications to education : an assessment - Zupata-Gorospe, Leticia (Manila : National University, 1996)
The improve the CDA program in its Manila Extension Office in the form of innovations or modifications. This study mays create increased awareness of the importance as well as the values derived from an organized and well-implemented CDA program. It may also serve as an effective tool in the development of CDA program, specifically among Administrators, Employees, and clients as well.
Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Method and Procedures of study -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive-Analytic.
Includes bibliographical references.